Tubular TiO2 Nanostructures: Toward Safer Microsupercapacitors. Issue 2 (23rd November 2017) - Salari, Maryam; Aboutalebi, Seyed Hamed; Ekladious, Iriny; Jalili, Rouhollah; Konstantinov, Konstantin; Liu, Hua Kun; Grinstaff, Mark W.
Abstract: Self‐organized tubular nanostructures, synthesized through straightforward and efficient techniques, are anisotropic materials, catalyzing many research breakthroughs, and, are of interest as electrode materials for electrochemical microdevices. The fabrication and characterization of microsupercapacitors composed of self‐assembled titanium dioxide (TiO2 ) nanotubes, as a combined current collector and electrode, are described. Moreover, conventional toxic acidic or alkaline electrolytes are not required, and the device operates with phosphate buffered saline as the electrolyte. Higher volumetric capacitance (84 F cm −3 ) and energy density (1.15 mWh cm −3 ) values are obtained with the anodized TiO2 microsupercapacitor devices compared with the conventional ones that employ carbon‐based electrodes and organic electrolytes. Achieving high capacitance through the use of a safe neutral aqueous electrolyte, combined with the biocompatibility of TiO2 and Ti films, opens up new avenues for the utilization of this system and its design for energy delivery or harvesting in biological and medical applications. Abstract : New material processing techniques such as anodization of metal sheets provide a method to miniaturize and integrate devices with 3D microarchitectures with precise control over porosity and microstructure. Miniaturized biocompatible TiO2 nanotube electrodes, when combined with phosphate buffered saline as the electrolyte, function as a microsupercapacitor.